2019
DOI: 10.3171/2018.2.jns172959
|View full text |Cite
|
Sign up to set email alerts
|

Surgical anatomy of the superior hypophyseal artery and its relevance for endoscopic endonasal surgery

Abstract: OBJECTIVE The endoscopic endonasal approach has become a routine corridor to the suprasellar region. The superior hypophyseal arteries (SHAs) are intimately related to lesions in the suprasellar space, such as craniopharyngiomas and meningiomas. Here the authors investigate the surgical anatomy and variations of the SHA from the endoscopic endonasal perspective. METHODS Thirty anatomical specimens with vascular injection were used for endoscopic endonasal dissection. The number of SHAs and their origin, course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Serious visual impairment could be caused by the covering of the superior hypophyseal artery. 19 In our series, the ophthalmic artery, anterior choroidal artery, and fetal-type posterior cerebral artery were not occluded by the covered stent, which may be attributed to appropriate case selection and careful evaluation of the location of the perforating arteries from multiple angles as well as the assistance of the two markers that point to the two ends of the Willis covered stent.…”
Section: Side Branch Occlusionmentioning
confidence: 68%
“…Serious visual impairment could be caused by the covering of the superior hypophyseal artery. 19 In our series, the ophthalmic artery, anterior choroidal artery, and fetal-type posterior cerebral artery were not occluded by the covered stent, which may be attributed to appropriate case selection and careful evaluation of the location of the perforating arteries from multiple angles as well as the assistance of the two markers that point to the two ends of the Willis covered stent.…”
Section: Side Branch Occlusionmentioning
confidence: 68%
“…The superior hypophyseal artery (SHA) originates from the ICA. Bilateral SHAs send out small branches to supply the lower surface of the optic chiasm, and branches from the ACAC provide the blood supply for the upper surface of the optic nerve 20,28 . Whether these blood vessels are preserved is closely related to the postoperative vision of patients 24 .…”
Section: Discussionmentioning
confidence: 99%
“…But whether occlusion of a unilateral SHA can lead to visual impairment is not known. In an anatomic study, Truong et al 28 showed that determination of visual outcome after occlusion of the SHA on one side was not possible. However, the overall impression was that the blood supply and vascular anastomosis of the optic nerve and optic chiasm were rich.…”
Section: Discussionmentioning
confidence: 99%
“…La superior es una rama de la carótida interna que irriga la pars tuberalis (la parte superior de la adenohipófisis que envuelve el tallo hipofisario), el infundíbulo y la eminencia media. La arteria hipofisaria inferior es una rama del tronco meningohipofisario de la arteria carótida interna, que ingresa por la parte posterior de la glándula 13 . Las arterias forman capilares que permiten el movimiento de nutrientes y hormonas y drenan hacia las venas portales.…”
Section: Las Células Hipofisarias Principales Sonunclassified